This is wrong, it only holds if is an odd prime number, which cannot be controlled in your question.phi(2n) = phi(n)
Note that . This might be useful.
Hi all, I've been stumped by this proof:
Prove that if n is any odd positive integer and k is a natural number such that n > 2^k, then phi(n) >= k + 1
So far I've only been able to use the fact that n is odd to say that phi(2n) = phi(n) since phi(2n) = phi(2) * phi(n). I'm not sure if this is even relevant, but it seems like it could be useful. Any help is appreciated.